Three dimensional printed models of the airway for preoperative planning of open Laryngotracheal surgery in children: Surgeon’s perception of utility - Oshri Wasserzug; Gadi Fishman; Narin Carmel-Neiderman; Yael Oestreicher-Kedem; Maher Saada; Solomon Dadia; Eran Golden; Philip Berman; Ophir Handzel; Ari DeRowe (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Preoperative planning of open laryngotracheal surgery is important for achieving good results. This study examines the surgeon’s perception of the importance of using life size 3D printed models of the pediatric airway on surgical decision making. Methods Life-size three-dimensional models of the upper airway were created based on CT images of children scheduled for laryngotracheal-reconstruction and cricotracheal resection with anastomosis. Five pediatric airway surgeons evaluated the three-dimensional models for determining the surgical approach, incision location and length, graft length, and need for single or double-stage surgery of seven children (median age 4.4 years, M:F ratio 4:3). They rated the importance of the three-dimensional model findings compared to the direct laryngoscopy videos and CT findings for each domain on a validated Likert scale of 1–5. Results The mean rating for all domains was 3.6 ± 0.63 (“moderately important” to “very important”), and the median rating was 4 (“very important”). There was full agreement between raters for length of incision and length of graft. The between-rater agreement was 0.608 (“good”) for surgical approach, 0.585 (“moderate”) for incision location, and 0.429 (“moderate”) for need for single- or two-stage surgery. Conclusion Patient-specific three-dimensional printed models of children’s upper airways were scored by pediatric airway surgeons as being moderately to very important for preoperative planning of open laryngotracheal surgery. Large–scale, objective outcome studies are warranted to establish the reliability and efficiency of these models. Graphical abstract